Il simbolo della croce tra giudeo-cristianesimo e tarda antichità: un elemento della translatio Hierosolymae - Loconsole, M. (Liber Annuus, 2003)
Abstract The cross, seen and exalted in a great many biblical or natural types and figures, entered the sacramental, cultic, and private lives of Christians already in the sub-apostolic period as a seal of God, a sign of Divine Presence, as salvation and protection. The early Christians prayed before the cross as a seal of God in the sacraments and a sign of eschatological salvation, possibly turned towards the east. They also placed the cross in their homes, in cultic places, and in cemeteries. Contrary to what is commonly held, the origin of the cross and its adoration are pre-Constantinian. Both are attested in the works of Minucius Felix and Tertullian, and confirmed by numerous testimonies from monuments. With Constantine, the honour and veneration of the cross became more noted and public. However the turning point of the cross from a sign of ignominy to a sign of glory cannot be attributed to the vision of the emperor. The cross was used by Christians already in the first years of the life of the Church, and the veneration of the cross goes back at least to the end of the 2nd century. It is an important confirmation that the cross was not an instrument of torture, but was venerated for its unique link with the life, mission and work of the Redeemer of humanity.